An Interactive Learning Of Process Control Through Simulation Of Heat Exchanger Using Matlab Simulink - Perumal, Suthasheny (Universiti Sains Malaysia, 2018)
Process engineer career is gaining importance in almost every industry worldwide. This is because, control system plays a huge role in every industry especially in many engineering industries. As such, our country requires competent process engineers to maintain the desired production capacity and at the same time ensure safety in a plant. However, many university students have little or no interest in learning process control subject. As such, many students restrict themselves from learning process control deeper as they have a mindset that process control is difficult to understand and boring. In this work, students opinions regarding process control subject was identified through a mixed-mode assessment method. The results obtained from the survey are analyzed. It shows that majority of the students prefer real-time simulation to be introduced in the teaching method of process control for them to understand process control better. Hence, a real-time virtual laboratory has been created for the simulation of heat exchanger using MATLAB Simulink. The students were asked to work on the simulation program and a post-simulation survey was created to obtain students feedback on the simulation program. The results from the survey show that 4 out of 9 participants with process control background and 5 out of 8 participants without process control background are able to score well in the quiz questions which were prepared from to test their understandings on this simulation programme.